The dominance entry of the principles of Gharar in electronic contracts - Razali, Siti Salwani (Brill Academic Publisher, 2009)
Contracts feature in all areas of our daily lives. For example, without much thought, we become party to a variety of contracts when we travel by bus or rail, purchase goods, accept services, and carry out our duties in the workplace. Contracts are so prevalent that ordinary men or women in the street do not realize the legal complexities of the transactions into which they enter. The use of Internet as a medium of communication has widened the scope for contract formation. Sales and purchase activities are conducted online using contracts either drawn up through the Internet itself or outside cyberspace. Several areas of uncertainty will have a significant impact on electronic contracting under Islamic Shari'ah law. This is a fundamental issue, especially with regard to online contracts for which the contracting parties are not physically present. In fact, if certain fundamental issues regarding online contracts are not resolved, then the dominance entry of the principles of ghārār (uncertainty) will apply, making such contracts unfeasible under Islamic Shari'ah law. Therefore, this paper aims to review what is actually meant by ghārār and how it affects the enforceability of electronic contracts under Shari'ah law. It also suggests how ghārār can be reduced or even eliminated to achieve an acceptable degree of certainty, thus enabling the practice of online contracts, particularly according to the Shari'ah.